Development of a ship route decision-making algorithm based on a real number grid method. (August 2020) - Kim, S.W.; Jang, H.K.; Cha, Y.J.; Yu, H.S.; Lee, S.J.; Yu, D.H.; Lee, A.R.; Jin, E.J.
Abstract: This research proposes a new route decision-making strategy, a real-number grid method, that challenges the state-of-the-art method in route decision-making. The key features of the proposed method compared to the conventional route decision making method are implementing a real number grid in the grid generation procedure, global speed optimization in the speed optimization procedure, and a Monte Carlo evaluation in the cost evaluation procedure. The newly suggested method not only improves the optimization performance of the conventional method but also upgrades constraint satisfaction in route decision making. The performance index of route decision making using the proposed method shows a noticeable difference compared to three-dimensional dynamic programming that is the state of art. For performance validation, an intuitively designed cost function is analyzed. The efficacy of this proposed method is proven based on a simulation of the mathematical cost function and actual voyage cases. The performance of the proposed method is demonstrated on a 173K LNG carrier in the Pacific and Atlantic Oceans. This proposed method demonstrates notable performance improvement in the simulation and actual voyage cases.